Data from multi-national aging cohorts show dysregulated metabolic pathways in people with physio-cognitive decline - Yi-Long Huang; Wei-Ju Chang; Chao-Hsiung Lin; Shu Zhang; Yukiko Nishita; Rei Otsuka; Wei-Ju Lee; Chih-Kuang Liang; Ming-Yueh Chou; Li-Ning Peng; Hidenori Arai; Luigi Ferrucci; et al. (Communications Medicine)
Abstract Background Physio-cognitive decline (PCD) represents a dual impairment of mobility and cognitive function in aging populations, significantly increasing risks of disability, dementia, and mortality. Despite its clinical importance, the underlying biological mechanisms driving PCD remain poorly understood. This study aimed to identify metabolomic biomarkers and pathways associated with PCD to elucidate potential mechanistic insights. Methods We conducted a comparative metabolomic analysis using serum samples from aging cohorts in Taiwan and Japan. A total of 197 pairs of participants were selected, comparing individuals in the top quintile (robust) versus bottom quintile (PCD) for both mobility and cognitive performance. Untargeted metabolomic profiling was performed to identify differential metabolites and dysregulated pathways. Results Here, we show significant alterations in 606 differential metabolites and 17 metabolic pathways in PCD individuals compared to robust controls. Key dysregulated pathways include glutathione metabolism, tryptophan metabolism, urea cycle/amino group metabolism, and bile acid biosynthesis. Eleven metabolites are confirmed as potential biomarkers, including creatinine, pyroglutamic acid, melatonin, 3-hydroxykynurenine, 5-hydroxytryptophan, taurodeoxycholic acid, glycocholic acid and 7α-hydroxycholesterol. Conclusions This study defines the comprehensive metabolomic signature of PCD, revealing disrupted metabolic pathways and identifying promising biomarker candidates for early detection and monitoring of physio-cognitive decline in aging populations.